2000
DOI: 10.1007/s004019900162
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line-derived neurotrophic factor protects against ischemia/hypoxia-induced brain injury in neonatal rat

Abstract: Ischemic/hypoxic brain damage induced in 7-day-old rats was significantly attenuated in a dose-dependent manner by intracerebral injection of glial cell line-derived neurotrophic factor (GDNF; 2 or 4 microg) within 30 min after the insult. Whereas the great majority of the vehicle-treated animals showed massive infarction involving more than 75% of the affected cerebral hemisphere, GDNF injection resulted in a remarkable reduction in both the incidence and severity of the brain damage (incidence ranging from 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…29 Upregulation of GDNF mRNA in the rodent brain has been shown to occur after excitotoxicity induced by glutamate, 30 kainate, 31 or ischemia. 5 GDNF has been shown to protect neurons against oxidative stress in cultured mesencephalic neurons and glial cells, 32 against ischemia-or hypoxia-induced brain injury in neonatal rats, 33 after brain injury following permanent or transient focal cerebral ischemia in rats or mice, 9,34 after cortical cold injury, 10 and in primate models of Parkinson's disease. 35 GDNF promotes cell survival in multiple ways; recent publications showed that GDNF upregulates antiapoptotic Bcl-2 and Bcl-X L levels in apoptosis-induced rat mesencephalic neurons, resulting in a reduction in caspase activation.…”
Section: Discussionmentioning
confidence: 99%
“…29 Upregulation of GDNF mRNA in the rodent brain has been shown to occur after excitotoxicity induced by glutamate, 30 kainate, 31 or ischemia. 5 GDNF has been shown to protect neurons against oxidative stress in cultured mesencephalic neurons and glial cells, 32 against ischemia-or hypoxia-induced brain injury in neonatal rats, 33 after brain injury following permanent or transient focal cerebral ischemia in rats or mice, 9,34 after cortical cold injury, 10 and in primate models of Parkinson's disease. 35 GDNF promotes cell survival in multiple ways; recent publications showed that GDNF upregulates antiapoptotic Bcl-2 and Bcl-X L levels in apoptosis-induced rat mesencephalic neurons, resulting in a reduction in caspase activation.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of GDNF mRNA in rat brains has been shown to occur following excitotoxicity induced by glutamate (Ho et al, 1995) or kainate (Humpel et al, 1994). GDNF has been shown to protect neurons against oxidative stress in cultured mesencephalic neurons and glial cells (Iwata-Ichikawa et al, 1999), against ischemic/hypoxic-induced brain injury in neonatal rats (Ikeda et al, 2000), after brain injury following permanent middle cerebral artery occlusion in rats (Kitagawa et al, 1998), and in primate models of Parkinson's disease (Kordower et al, 2000). The mechanisms by which GDNF exerts its neuroprotective effect are diverse, and recent evidence demonstrates that the rescue and repair of injured neurons is a consequence of an antiapoptotic action of GDNF.…”
Section: Figmentioning
confidence: 99%
“…HO-1 is also induced by fibroblast growth factor-1 in spinal cord astrocytes [23]. In a model of ischemia/hypoxia-induced brain injury, GDNF was shown to significantly reduce HSP70 induction [24,25]. After spinal cord injury, up-regulation of HSP72 was considerably reduced in brain-derived neurotrophic factor-(BDNF) or insulin like growth factor-1-pretreated rats [26].…”
mentioning
confidence: 99%